Design and performance verification of crab seedling automatic counting equipment based on improved YOLOv11+DeepSORT - Changfeng Tian; Xuan Che; Lei Ge; Zhi Qu; Mengxia Han (Aquacultural Engineering, 2026)

Synergistic regulation of oxygen vacancies and surface hydroxyl groups in Fe-doped CeO2 for enhanced fluoride adsorption - Shidong Zheng; Yufei Shu; Chaoqun Zhu; Beizhao Chen; Youmei Xu; Weiwen Chen; Mengxia Wang; Siyu Cao; Zhipeng Liu; Fan Wang; Yunjiao Han; Zhongying Wang (Chemical Engineering Journal, 2026)

Dual roles of N6-methyladenosine in R-loop regulation of gene transcription and genome stability - Fangle Li; Feifan Zhang; Jie Li; Yu Zhang; Wenxuan Gong; Yawei Zhang; Mengxia Liu; Jie Ren; Dali Han (Science China Life Sciences, 2025)

Development and multi-objective optimization of a solar-powered hybrid aerator for aquaculture - Zhi Qu; Changfeng Tian; Xuan Che; Mengxia Han; Yin Zhou (Aquacultural Engineering, 2025)

Glycine-mediated heavy metal leaching and calcium retention from municipal solid waste incineration fly ash: A mechanistic study - Hailong Li; Zhenyao Xu; Yaqi Peng; Mengxia Xu; Hongxian Li; Zhongkang Han; Shengyong Lu; Jianhua Yan (Journal of Environmental Management, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Cation-free siRNA micelle knockdown of EPHA2 improves sensitivity of imatinib for osteosarcoma treatment - Yunlong Wang; Mengting Wang; Jianhui Yang; Mengxia Liang; Heqing Liu; Lei Wang; Ao Peng; Yufei Xiang; Ruixiang Huang; Yongfei Dong; Deliang Gong; Han Xie; et al. (Chemical Engineering Journal, 2025)

Comparison of microplastics heteroaggregation with MoS2 and graphene oxide nanosheets: Dependence on the configuration and impacts on aquatic transport - Mengxia Wang; Xun Liu; Meng Zhang; Qi Han; Beizhao Chen; Siyu Cao; Bei Liu; Zhongying Wang (Journal of Hazardous Materials, 2025)

Electrochemical destruction of PFAS at low oxidation potential enabled by CeO2 electrodes utilizing adsorption and activation strategies - Xun Liu; Yufei Shu; Yu Pan; Guoshen Zeng; Meng Zhang; Chaoqun Zhu; Youmei Xu; Aling Wan; Mengxia Wang; Qi Han; Bei Liu; Zhongying Wang (Journal of Hazardous Materials, 2025)

Numerical Simulation and Experimental Study of a Small-Scale Vacuum Fish Pump - Changfeng Tian; Zhi Qu; Xuan Che; Mengxia Han; Yin Zhou; Fan Wu (Journal of Marine Science and Engineering, 2024)
The existing vacuum fish pump is too large and difficult to move, which is difficult to apply to small fishing vessels. However, the development of a small vacuum fish pump is not a single scaling of the existing vacuum fish pump but requires the support of relevant experiments and simulation theories. In this study, a vacuum fish pump suitable for small fishing vessels was developed. Firstly, a numerical model of the internal flow field during the vacuum fish pump’s working process was established using computational fluid dynamics (CFDs) and verified its effectiveness by physical experiments. It is found that the VOF model can well predict the variation of the volume fraction of the liquid phase in the whole calculation area with time during the suction or drainage process of the vacuum fish pump. Then, the internal flow field characteristics of the fish pump under different working conditions were simulated, and the rationality of the design of the fish pump was evaluated according to the numerical results. Finally, a separate physical experiment was carried out on grass carp, carp, crucian carp, silver carp, and bighead carp, respectively, and the capture efficiency and corresponding fish damage rate for different fish were analyzed. The experimental and numerical results show that the vacuum suction fish pump can achieve efficient and automatic suction and transport of live fish.

In situ remediation of mercury-contaminated groundwater through an in situ created reactive zone enabled by carboxymethyl cellulose stabilized FeS nanoparticles - Mengxia Wang; Bing Han; Dongye Zhao; Sen Hou; Weizhao Yin; Yanyan Gong (Environmental Pollution, 2024)

Influences of substrate pore size on the morphology and separation performance of MoS2-interlayered thin-film nanocomposite membranes - Siyu Cao; Li Wang; Yufei Shu; Meng Zhang; Mengxia Wang; Qi Han; Xun Liu; Zhongying Wang; How Yong Ng (Desalination, 2024)

Insights into microbial metabolic coordination under driving force of different conductive materials-mediated direct interspecies electron transfer during anaerobic digestion - Xinwei Zhou; Mengxia Guo; Xiangzhuang Fu; Dexin Wang; Jianjun Liao; Wen Xu; Hongjun Han (Chemical Engineering Journal, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Efficient remediation of mercury-contaminated groundwater using MoS2 nanosheets in an in situ reactive zone - Mengxia Wang; Qi Han; Meng Zhang; Xun Liu; Bei Liu; Zhongying Wang (Journal of Contaminant Hydrology, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Selective fluoride removal from groundwater using CNT-CeO2 electrodes in capacitive deionization (CDI) - Xun Liu; Danyal Rehman; Yufei Shu; Bei Liu; Li Wang; Li Li; Mengxia Wang; Kunkun Wang; Qi Han; Linlin Zang; John H. Lienhard; Zhongying Wang (Chemical Engineering Journal, 2024)

Integration of Sentinel–1 and Landsat–8 data for identifying deformation risk of hydraulic engineering in seasonally frozen salinization regions - Zhaoxi Wang; Chen Cao; Qingbo Yu; Xin Xu; Qing Wang; Cencen Niu; Jiejie Shen; Mengxia Han; Huicheng Fu; Kuanxing Zhu; Jing Liu; Weitong Xia; et al. (CATENA, 2023)

The impact of redox annealing on intrinsic properties and fluoride adsorption performance of CeO2 nanomaterials - Yu Pan; Xun Liu; Meng Zhang; Qi Han; Yufei Shu; Mengxia Wang; Bei Liu; Zhongying Wang (Chemical Engineering Journal, 2023)

Quantifying the late Quaternary incision rate in the upper Jinsha River with dated fluvial terraces and transient tributary profiles - Zhihai Li; Jianping Chen; Zhigang Shan; Yiding Bao; Yuchao Li; Kun Shan; Di Liu; Mengxia Han (CATENA, 2023)

Quantitative evaluation of drought risk related to vegetation productivity in China - Wenyan Ge; Xiuxia Li; Mengxia Xie; Bowen Yu; Juying Jiao; Jianqiao Han; Fei Wang (Journal of Hydrology, 2023)

Analysis of the pore structure characteristics of saline soil in the profile within the frozen depth - Zhaoxi Wang; Chen Cao; Qing Wang; Jiejie Shen; Mengxia Han; Weitong Xia; Tian Zhou; Zhongyu Yu; Xuehan Shan (Cold Regions Science and Technology, 2023)

Micro–composition evolution of the undisturbed saline soil undergoing different freeze–thaw cycles - Mengxia Han; Wei Peng; Bing Ma; Qingbo Yu; Kiyonobu Kasama; Zentaro Furukawa; Cencen Niu; Qing Wang (Cold Regions Science and Technology, 2023)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

Description of different cracking processes affecting dispersive saline soil slopes subjected to the effects of frost and consequences for the stability of low slopes - Mengxia Han; Qing Wang; Yan Han; Huicheng Fu; Jiejie Shen; Yaowu Liu (Bulletin of Engineering Geology and the Environment, 2022)

Numerical simulation and analysis of a geological disaster chain in the Peilong valley, SE Tibetan Plateau - Zhihai Li; Fujun Zhou; Xudong Han; Jianping Chen; Yuchao Li; Shijie Zhai; Mengxia Han; Yiding Bao (Bulletin of Engineering Geology and the Environment, 2021)